2005
DOI: 10.1159/000086363
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia and Insulin Insensitivity in Women with Nonclassical Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency: The Relationship between Serum Leptin Levels and Chronic Hyperinsulinemia

Abstract: Background/Aim: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency (NC-CAH) is associated with hyperandrogenemia, chronic anovulation, hirsutism, acne and adrenal hyperplasia. A few studies have shown hyperinsulinemia and insulin insensitivity in NC-CAH. Hyperinsulinemia can stimulate leptin secretion, and androgens can inhibit leptin secretion. Thus, we designed a study to investigate the insulin levels and insulin sensitivity and the effect of chronic endogenous hyperinsulinemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 67 publications
7
60
2
2
Order By: Relevance
“…The present report adds further support to the notion that vitamin D repletion/supplementation may be a valid treatment for insulin resistance and its associated comorbidities in the context of vitamin D deficiency/ insufficiency. It reinforces several emerging concepts: (1) Insulin resistance is associated with a number of conditions, such as non-classic 21-hydroxylase deficiency [7,8]; (2) interventions likely to improve insulin sensitivity often ameliorate co-morbidities associated with insulin resistance; (3) serum vitamin D is often deficient/insufficient in insulin resistant individuals; (4) disorders associated with insulin resistance may be mitigated in association with vitamin D repletion.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The present report adds further support to the notion that vitamin D repletion/supplementation may be a valid treatment for insulin resistance and its associated comorbidities in the context of vitamin D deficiency/ insufficiency. It reinforces several emerging concepts: (1) Insulin resistance is associated with a number of conditions, such as non-classic 21-hydroxylase deficiency [7,8]; (2) interventions likely to improve insulin sensitivity often ameliorate co-morbidities associated with insulin resistance; (3) serum vitamin D is often deficient/insufficient in insulin resistant individuals; (4) disorders associated with insulin resistance may be mitigated in association with vitamin D repletion.…”
Section: Discussionsupporting
confidence: 70%
“…Although his infection certainly improved he remained under a great deal of stress as a result of postsurgical pain and phantom pain associated with his amputation as well as the prospect of lengthy rehabilitation and considerable loss of income and mounting hospital bills during this period, thus his HPA axis likely remained very active. Beyond these considerations, as discussed in references [3,4,8]. We have reported these types of rapid responses to a number of insulin-sensitizing interventions.…”
Section: Discussionmentioning
confidence: 86%
“…Glucocorticoids, the foundation of CAH treatment, is often given in supraphysiological doses to normalize the adrenal androgens, which may lead to unfavorable metabolic consequences: obesity, insulin resistance with type 2 diabetes (T2DM), and hypertension. Longstanding undertreatment with elevation of adrenal androgens may also reduce insulin sensitivity (8,9) and induce hypogonadism with low testosterone values by gonadotropin suppression. Hypogonadotropic hypogonadism has been shown to be a risk factor for the metabolic syndrome and T2DM and to increase cardiovascular mortality (10).…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate mineralocorticoid therapy for aldosterone deficiency may also have negative impact on the vascular system (11). Previous reports on cardiovascular and metabolic profiles in CAH adults have mainly included young females, in spite of the fact that males in general have a higher cardiovascular risk, and the results have been contradictory (6,8,9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A very recent publication described however a cohort of 203 individuals with CAH including 62 males reporting adverse metabolic profiles (23).…”
Section: Introductionmentioning
confidence: 99%
“…Of the few studies that have explored insulin sensitivity in CAH, most have concluded that CAH patients are indeed characterized by insulin resistance (5)(6)(7)(8)(9)(10)(11). Many different methods have been used to assess insulin sensitivity, but studies using the euglycemic hyperinsulinemic clamp method, the gold standard to assess insulin sensitivity, are lacking.…”
Section: Introductionmentioning
confidence: 99%